A comparative history of motor fuels taxation, 1909-2009 : why gasoline is cheap and petrol is dear - Geschwind, Carl-Henry, 1965- (Lexington Books, 2017)
This study examines gasoline taxation policies since the early twentieth century. Comparing and contrasting policies in the United States, Germany, the United Kingdom, and New Zealand, the author analyzes the origins of gasoline taxation and the various approaches to its implementation and highlights the role played by fiscal crises.